Structural Approach to Revision Rhinoplasty - Katrib, Ziad A. (Facial Plastic Surgery, 2025)
To explain a very clear and concise, systematic approach to revision rhinoplasty from the preoperative visit, to the operation, and finally to the postoperative course.All pertinent anatomy is discussed both in the preoperative examination, and in the technical details describe in the operation. Images accompany all key maneuvers for further clarification.We discuss the key physical examination findings, functional analysis, and standardized photography of the patient prior to the operation.We describe the key foundational techniques utilized from start to finish to design and construct the most stable, functional, and aesthetic nose possible in a revision rhinoplasty. We discuss anesthesia, as well as intraoperative splints and dressings.We review all postoperative care given to our patients, as well as the reasoning behind these instructions.We provide an easy-to-follow, step-by-step logical approach to revision rhinoplasty. Despite the nearly endless combination of possible findings once in the operation, by following these guiding principles the operation can be completed in a consistent, efficient, and thorough manner.
Keywords: revision rhinoplasty; rib; rib graft; lateral crural strut graft; SPF graft